Tax Litigation and Corporate Debt: A Brazilian Perspective - Lopo Martinez, Antonio; Coutinho, Julia; Formigoni, Henrique; Santos, Luis Paulo (Advances in Scientific and Applied Accounting, 2024)
Objective: The study aims to explore the impact of tax litigation on the indebtedness levels of Brazilian firms. The research is motivated by Brazil’s high volume of tax disputes and the lack of existing studies focusing on the relationship between tax litigation and firm indebtedness in this particular context. Method: The sample includes non-financial firms listed on the Brazilian stock exchange from 2017 to 2022. Linear regression methodology, utilizing panel data and fixed effects, was employed to analyze the relationship. Tax litigation was quantified by summing tax provisions and contingent liabilities, which were then relativized by the firms’ total assets. Data were sourced from Comdinheiro software, with additional information manually gathered from company explanatory notes. Results or Discussion: The study found a positive relationship between tax litigation and firm indebtedness in Brazil. This suggests that companies involved in more tax disputes tend to have higher levels of debt, pointing towards a complex relationship between the two variables in the Brazilian economic landscape. Contributions: This research fills a gap in existing literature by investigating the effects of tax litigation on the capital structure of Brazilian firms. It provides valuable insights that can be beneficial for policymakers, regulatory bodies, and firms in understanding the implications of tax disputes on financial strategies.